2023
DOI: 10.3390/biology12030400
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Galactic Cosmic Rays on the Central Nervous System: From Negative to Unexpectedly Positive Effects That Astronauts May Encounter

Abstract: Galactic cosmic rays (GCR) pose a serious threat to astronauts’ health during deep space missions. The possible functional alterations of the central nervous system (CNS) under GCR exposure can be critical for mission success. Despite the obvious negative effects of ionizing radiation, a number of neutral or even positive effects of GCR irradiation on CNS functions were revealed in ground-based experiments with rodents and primates. This review is focused on the GCR exposure effects on emotional state and cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 204 publications
1
3
0
Order By: Relevance
“…An important issue is to uncover the cellular and molecular mechanisms responsible for the preservation of sensorimotor cortex volume in irradiated rats. In line with existing literature data [1], the damage properties of IR and, in particular, HZE are undeniable. At the same time, a lesion in the neocortex induces a transient increase in the proliferation as well as neurogenesis in the subventricular zone.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…An important issue is to uncover the cellular and molecular mechanisms responsible for the preservation of sensorimotor cortex volume in irradiated rats. In line with existing literature data [1], the damage properties of IR and, in particular, HZE are undeniable. At the same time, a lesion in the neocortex induces a transient increase in the proliferation as well as neurogenesis in the subventricular zone.…”
Section: Discussionsupporting
confidence: 77%
“…Studies have shown that such low-dose low-LET pre-irradiation significantly modulates the organism's response to irradiation by HZE [68]. When choosing the HZE component, we relied on the fact that 12 C 6+ is the most common nucleus after H + and 4 He 2+ in the composition of GCR [69], while the LET value was near the median value on the GCR LET spectrum measured on the Mars surface and during the Earth-Mars cruise [1]. Based on the dosimetric study, low-LET exposure will be predominant during spaceflight Moreover, during the realization of crewed deep-space missions, more advanced shielding will be used, which will also shift the particle spectrum towards the low-LET component and may reduce the equivalent dose by up to 30% [71,72].…”
Section: Irradiation Procedures and Dosimetrymentioning
confidence: 99%
See 2 more Smart Citations